New Developments in Hypertrophic Cardiomyopathy - Cooper, Robert M; Raphael, Claire E; Liebregts, Max; Anavekar, Nandan S; Veselka, Josef (The Canadian journal of cardiology, 2017)
Hypertrophic cardiomyopathy is the leading cause of sudden death in young individuals and an important cause of heart failure at any age. In this review we discuss advances in investigation and management of this heterogenous disease. Improved cardiac imaging has allowed us to detail many of the structural abnormalities whereas the use of new techniques, predominantly in cardiac magnetic resonance imaging, has given us a greater insight in to tissue architecture, mechanism of contractile abnormalities, and function. Risk stratification remains challenging because of the low event rate in clinical studies. Multicentre registries have improved risk stratification for sudden cardiac death and multiple models can be used to aid decision-making for implantable defibrillator therapy. We discuss the current state of nonsurgical septal reduction therapy and results of multicentre registries. New approaches to septal reduction therapy including refinement of alcohol ablation and noncoronary interventions such as radiofrequency ablation of the septum show great promise. Surgical myectomy remains a major part of treatment; a greater recognition of abnormalities of the mitral valve apparatus can allow improved surgical options. Myocardial perfusion abnormalities are known to predict adverse outcome in hypertrophic cardiomyopathy and we discuss underlying mechanisms and relevance to management. The off-label use of currently licensed medicines such as ranolazine, perhexiline, calcium channel blockers, and renin-angiotensin system antagonists are discussed. A novel approach to medical treatment of the underlying sarcomeric disorder has been investigated and shows great potential.
Keywords: Disease Management; hypertrofická kardiomyopatie; Defibrillators, Implantable; Incidence; náhlá srdeční smrt; magnetická rezonance kinematografická; katetrizační ablace; Magnetic Resonance Imaging, Cine; incidence; míra přežití; Cardiomyopathy, Hypertrophic; management nemoci; Catheter Ablation; Humans; Survival Rate; celosvětové zdraví; defibrilátory implantabilní; Death, Sudden, Cardiac; srdeční selhání; Global Health; Heart Failure; lidé